Analysis Of Cucumber Food In Rainfall Land In Percut Sei Tuan District - Adriansyah Adriansyah; Henny Wahyuni (JASc (Journal of Agribusiness Sciences), 2020)
Most agricultural land in Indonesia is used for growing vegetables. One of the vegetables that is being ferociously grown today is cucumber. Farming is the process of organizing the factors of production, namely nature, labor, capital and management that is cultivated by individuals or groups of people to produce output that can meet the needs of families or other people in addition to the motive for profit. One characteristic of the lives of farmers is the different patterns of income and expenditure. The area of agricultural land will affect the scale of business which will ultimately affect the efficiency or not of an agricultural business. The purpose of this study is to determine the economic factors that affect the income of cucumber farmers, and to find out the social factors that affect the income of cucumber farmers. From the results of the study it was found that the R / C ratio of cucumber farming was 2.15, this showed that cucumber farming in Tumpatan Nibung village was feasible to be develope